The Impact of 11 Sessions of 4v4+1+Target Training Can Enhance Pass Accuracy Short-Passing Accuracy in Adolescent Football Players - Hanief, Yulingga Nanda; Setiawan, Yoga Ridho Agus (Universitas Negeri Semarang, 2024)
Short-passing accuracy is one of the keys to converting opportunities into goals, but mastering short-passing accuracy is still a significant problem for adolescent football players. This study aims to determine the impact of small-sided games (SSG) training with 4v4 + 1 + target format on improving short-passing accuracy in adolescent football players. This study is a quantitative descriptive study with a pre-experimental approach and uses a one-group pretest-posttest. The participants in this study were 12 adolescent athletes aged 14-16 years (15.2 ± 1.51) at Surya Muda Football Academy, Blitar City. The short-passing accuracy test was used to determine short-passing accuracy. The data that has been obtained was analyzed using a t-test with the help of SPSS. The results showed that 4v4+1+target training for 11 meetings could improve short-passing accuracy (Sig. 0.001 <0.05). In conclusion, 4v4+1+target SSG training can improve short-passing accuracy in adolescent football players and athletes. Exploration of other SSG formats needs to be investigated for their impact on football playing skills and improving physical and psychological conditions.